2018
DOI: 10.5194/esd-9-563-2018
|View full text |Cite
|
Sign up to set email alerts
|

Estimating sowing and harvest dates based on the Asian summer monsoon

Abstract: Abstract. Sowing and harvest dates are a significant source of uncertainty within crop models, especially for regions where high-resolution data are unavailable or, as is the case in future climate runs, where no data are available at all. Global datasets are not always able to distinguish when wheat is grown in tropical and subtropical regions, and they are also often coarse in resolution. South Asia is one such region where large spatial variation means higher-resolution datasets are needed, together with gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…S5). Crop calendar improvements at high spatial resolution, such as recently published for rice ( 50 ), are expected to further improve crop yield simulations—especially in regions where growing seasons are closely linked to the onset of the rainy season ( 51 , 52 ). There is no global information about temporal variations in growing season, but recent studies show that the implementation of high-quality crop development dates reported annually for the United States even allows for a historical reproduction of observed temporal trends in U.S. yields ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…S5). Crop calendar improvements at high spatial resolution, such as recently published for rice ( 50 ), are expected to further improve crop yield simulations—especially in regions where growing seasons are closely linked to the onset of the rainy season ( 51 , 52 ). There is no global information about temporal variations in growing season, but recent studies show that the implementation of high-quality crop development dates reported annually for the United States even allows for a historical reproduction of observed temporal trends in U.S. yields ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…2, Eq. 1 and Osborne et al (2015); Mathison et al (2018)). It is recommended for sequential cropping to prescribe a latest possible harvest date for those instances where the crop does not develop quickly enough and therefore does not reach maturity before the next crop in the rotation is due to be sown.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The India simulations focus on the north Indian states of Uttar Pradesh and Bihar. These states are key producers of rice and wheat in India and the use of a rice-wheat rotation is prevalent in this part of India (Mahajan and Gupta, 2009 not require a vernalization period which is important for winter wheat varieties (Griffiths et al, 1985;Robertson et al, 1996;Mathison et al, 2018). We select four points across these two states in order to gain understanding of the model response, particularly in terms of yield, to the variation in the conditions across the two states.…”
Section: India Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the planting date is one of main inputs as management information in process-based crop models [11][12][13]. There are many different methods to determine planting dates as an input to crop models [11][12][13][14][15][16]. One main method uses actual or simulated weather data to define rule-based planting dates [11,13,14].…”
Section: Introductionmentioning
confidence: 99%